Edukasi Prospek Karier bagi Mahasiswa Ilmu Komunikasi Melalui Program Talk Show di Radio Assalam UIN Ar-Raniry - Al Zuhri; Hanifah Hanifah; Anhar Fazri; Desi Maulida; Saiful Amri; Agus Pratama; Heri Rahmatsyah Putra (Universitas Teuku Umar, 2022)
Today's work climate has metamorphosed very dynamically, the human resources produced have also skyrocketed, but it does not match the available job vacancy. This becomes a problem every year as if there is no common ground. The implementation of Community Service facilitated by Assalam radio is directed to answer the above problems by providing enlightenment to prospective students, prospective alumni, and alumni of Communication Studies to be aware and ready for the realities of the existing job opportunities. Community Service was delivered in a talk show format, guided directly by Assalam practitioners. The initiators who also fill the program are two lecturers, one from Communication Studies, Teuku Umar University and the other from Islamic Communication and Broadcasting, State Islamic University Ar-Raniry. The results and conclusions that can be conveyed are that community service that was initiated runs smoothly with the support of complete broadcast media. Then the author views that dissemination or socialization in various formats is very important to be initiated for prospective students, prospective alumni, and alumni of Communication Studies so that they better understand the direction and job situation of the major taken. Because many of them are still pessimistic and confused about the majors that they have or are currently pursuing, whether they will get a job or not, there are great opportunities or not, promising or not, will become practitioners or academics, and other issues.